A hydrothermal pathway for TiO2-rGO heterojunction nanocomposite to enhance hydrogen peroxide evolution - Hoang Lin, Tong; Minh Huong, Le; Quang Cong, Che; Hoai Nam, Nguyen Thanh; Tan Thinh, Nguyen; Yen Oanh, Doan Thi; Huu Hieu, Nguyen (Vietnam Journal of Science and Technology, 2025)
In this study, titanium dioxide-reduced graphene oxide (TiO2-rGO(TGO)) nanocomposite was synthesized via hydrothermal pathway. The characterization of the fabricated material revealed an efficient incorporation of the two constituents, as well as a notable decrease in the band gap energy of TGO compared to that of pristine TiO2 (2.62 versus 3.15 eV, respectively), which can expand the absorption spectrum of the catalyst towards the visible region. Electrochemical studies also elucidated the contribution of the rGO substrate in prolonging the recombination rate of charge carriers, signifying a noticeable enhancement in the photocatalytic capability of the TGO composite. Meanwhile, the hydrogen peroxide evolution performance of the synthesized photocatalyst was relatively promising with a concentration of up to 158.34 μM after 180 min. Along with further examinations additionally showing the plausible formation and participation of reactive oxygen radicals during the photocatalytic scheme, the TGO material indicates a good potential for several practical applications, especially the generation of hydrogen peroxide under light irradiation.